2014
DOI: 10.1002/hyp.10373
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the temporal relation of remotely sensed coastal water quality with GIS modelled upstream soil erosion

Abstract: Hydrological processes at the river basin influence the quality of downstream water bodies by controlling the loads of nutrients and suspended solids. Although their monitoring is important for social, economic and environmental reasons, in-situ measurements are too expensive and thus too sparse to describe their relations. The aim of this study is to investigate the temporal relations of soil erosion in the upstream part of river basins with water quality characteristics in the downstream coastal zone, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Similar approaches, i.e. modeling soil erosion with GIS, have been also successfully implemented at a river basin in Northern Greece [16].…”
Section: Universal Soil Loss Equation (Usle)mentioning
confidence: 99%
“…Similar approaches, i.e. modeling soil erosion with GIS, have been also successfully implemented at a river basin in Northern Greece [16].…”
Section: Universal Soil Loss Equation (Usle)mentioning
confidence: 99%
“…The needs of natural environment managers go beyond these divisions because it would be nonsense to fight coastal erosion without also acting upstream in the watershed. Integrated source-to-sink studies where models of hydrologists and oceanographers interact are still scarce but they are just starting (see, e.g., [338,339]); • integration of time and space scales for long-term landscape changes [178,183,340], and filling the gap between stratigraphic models and process-based sediment transport models [25,341,342]. Now, interdisciplinary approach is expanding beyond nature and life sciences when their topic join societal concerns.…”
Section: A Topic That Moves Forward Through Interdisciplinary Approachesmentioning
confidence: 99%
“…Earth observation together with national statistics, field-based observations, and numerical simulation models are designated as the main source of information for the global monitoring of ecosystem services [29]. A recent study demonstrated that environmental parameters, such as chlorophyll-a (Chl-a) and total suspended matters (TSM), can be investigated at river basin scale through direct and indirect remote sensed observations [30]. On the other hand, in situ measurements for various ecological parameters are limited to a few experiments sites due to severe economic cost, difficulty in accessing the area of interest and a posteriori highly laborious procedures.…”
Section: Satellite Remote Sensingmentioning
confidence: 99%